The cluster concept as a multi-dimensional thematic field: Methodological and substantive perspectives - Thomas Stahlecker; Henning Kroll (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2012)
The empirical sub-sections of this article have shown that the both production and technology oriented clusters are a very diverse and regionally embedded phenomenon. Within this context, the observed diversity of political strategies and support measures whose ultimate goal is to 'generate cluster advantages' cannot genuinely surprise, even if its remains criticized by academics (Kiese 2007; Martin/Sunley 2003).
urn:nbn:de:0011-n-2100594
Keywords: 330; Regionales Cluster; Messung; Wissenschaftliche Methode; Theorie; Deutschland